Implementation of Da'wah Training Management in Improving the Competence of Da'i Nagari West Sumatra - Asep Iwan Setiawan; Vici Ramadini Yunus; Ahmad Sarbini (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to analyze the process of planning, organizing, implementing, and supervising da'wah training in the Da'i Nagari program under the guidance of BAZNAS, Tanah Datar Regency, West Sumatra. The research uses a qualitative approach through a descriptive study. Data were collected through observation, interviews, and literature study. The study results concluded that there was an implementation of the management function in the Da'i Nagari program. This can be reviewed in the planning aspect through the analysis process of the analysis of the training objectives, training participants, the budget allocated for running the program, training facilities and infrastructure, as well as the time and schedule of training activities; the organizing aspect is carried out through a small team as the person in charge consisting of three people; implementation aspects concerning the planning of training programs; and aspects of supervision by involving parties who act as supervisors of training activities. This research has implications for an increase in the competence of preachers both in intellectual, social, and spiritual aspects.Penelitian ini bertujuan untuk menganalisis proses perencanaan, pengorganisasian, pelaksanaan, dan pengawasan pelatihan dakwah pada program Da’i Nagari binaan BAZNAS Kabupaten Tanah Datar Sumatera Barat. Penelitian menggunakan pendekatan kualitatif melalui studi deskriptif. Pengumpulan data dilakukan melalui observasi, wawancara, dan studi pustaka. Hasil penelitian menyimpulkan bahwa terdapat implementasi fungsi manajemen pada program Da’i Nagari. Hal ini dapat ditinjau pada aspek perencanaan melalui proses analisis analisis tujuan pelatihan, peserta pelatihan, anggaran biaya yang diperuntukan untuk menjalankan program, sarana dan prasarana pelatihan, serta waktu dan jadwal kegiatan pelatihan; aspek pengorganisasian yang dilakukan melalui tim kecil sebagai penanggungjawab yang terdiri dari tiga orang; aspek pelaksanaan dengan merujuk pada perencanaan program pelatihan; dan aspek pengawasan dengan melibatkan pihak yang berperan sebagai pengawas kegiatan pelatihan. Penelitian ini berimplikasi pada adanya peningkatan kompetensi da’i baik pada aspek intelektual, sosial, dan spiritual.